THE MAINTENANCE OF STRIPED CATFISH (Pangasius hypopthalumus) IN BIOFLOCS TECHNOLOGY WITH PROBIOTICS DOSAGE DIFFERENT - Sahad Ganda Siburian; Rusliadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from May until June 2016 at Laboratory Aquaculture ofTechnology Faculty Fisheries and Marine Science, University of Riau. The purpose of thisresearch was to investigate growth and survival rate of striped catfish with probiotics dosage isdifferent in bioflocs techniques. This research using experimental method and completelyrandom design (RAL) one factor with three treatment there are P0: without giving probiotics(control), P1: probiotics giving 5 ml/m3, P2: probiotics giving 10 ml/m3, P3: probiotics giving 15ml/m3. The result showed that maintenance striped catfish with probiotics dosage is differentgiving affect significantly on the growth of absolute weight, absolute length growth, but notaffect significantly on the survival rate and food efficiency, specific growth rate and foodconversation rate (FCR). The best treatment were obtained in treatment three (P3) withprobiotics dosage giving 15 ml/m3 with value growth of absolute weight 7,08 gram, growth inabsolute length 3,85 cm, specific growth rate 3,69 %, food efficiency (EP) 70,06 %, foodconversation rate (FCR) 1,51, flock volume 2,1 ml and survival rate 58 %.Keyword : maintenance fish with probiotics dosage giving is different